2003
DOI: 10.3201/eid0902.020185
|View full text |Cite
|
Sign up to set email alerts
|

Life-Threatening Infantile Diarrhea from Fluoroquinolone-ResistantSalmonella entericTyphimurium with Mutations in BothgyrAandparC

Abstract: Salmonella Typhimurium DT12, isolated from a 35-day-old infant with diarrhea, was highly resistant to ampicillin, tetracycline, chloramphenicol, streptomycin, gentamycin, sulfamethoxazole/trimethoprim, nalidixic acid, and fluoroquinolones. The patient responded to antibiotic therapy with fosfomycin. Multidrug-resistance may become prevalent in Salmonella infections in Japan, as shown in this first case of a patient infected with fluoroquinolone-resistant Salmonella.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 17 publications
0
39
0
2
Order By: Relevance
“…For all the isolates, fluoroquinolone MICs were 24 g/ml or more, indicating a high level of resistance (Table 2). Sequence analysis of the QRDRs of the gyrA, gyrB, parC, and parE genes revealed that all but one isolate harbored the same combination of three point mutations, two in GyrA (S83F, TCC to TTC; and D87N, GAC to AAC) and one in ParC (S80R, AGC to CGC), which are the same as those found in the first isolate ( Table 2, isolate 0) (13). For one isolate (no.…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…For all the isolates, fluoroquinolone MICs were 24 g/ml or more, indicating a high level of resistance (Table 2). Sequence analysis of the QRDRs of the gyrA, gyrB, parC, and parE genes revealed that all but one isolate harbored the same combination of three point mutations, two in GyrA (S83F, TCC to TTC; and D87N, GAC to AAC) and one in ParC (S80R, AGC to CGC), which are the same as those found in the first isolate ( Table 2, isolate 0) (13). For one isolate (no.…”
Section: Resultsmentioning
confidence: 70%
“…Furthermore, reports of quinolone-resistant strains of serovar Typhimurium, with decreased susceptibility to fluoroquinolones, are increasing, and such organisms may cause difficulty in the treatment of infections (12,17). In 2000, we identified a high-level fluoroquinolone-resistant serovar Typhimurium isolate in a patient (13). High-level resistance to fluoroquinolones has been reported in other countries as well (3,7,11).…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Recent reports suggest that high level FQ resistance is re-emerging in S. Typhimurium, S. Choleraesuis, and S. Schwarzengrund in different parts of the world [28,76,102,111]. Polyclonal re-emergence of high level FQ-resistance is not only reflected by the several serotypes in which this resistance is now encountered, but also by the diversity of the target gene mutations identified: two different double mutations in gyrA [111], one single mutation in gyrB [28], three different single mutations in parC [102], and for the first time one single mutation in parE [87].…”
Section: Re-emergence Of High-level Fluoroquinolone Resistancementioning
confidence: 99%